Design and Simulation of Differential Protective Relay (DPR) to 33/11kv Delta-Wye Transformer Using Saber Software Simulator - Othman, Muhammad Murtadha (2000)
Substation automation constitutes the integral part of distribution automation. An automated distribution system may require many remote and central intelligent controllers or computers running synchronously in a very large boundary that are capable of making decisions and performing control actions. A protective relay is a device that responds to abnormal conditions in an electrical power system to operate a circuit breaker to disconnect the faulty section of the system with the minimum interruption of supply. Reliability, speed and selectivity are the most desirable characteristics of a protective relay. Numerical relays play an essential role in various distribution automation functions, and instead of mere protection relays it is also able to interact with the other instruments. In most utilities, power transformers often represent the expensive and also the largest capital purchase in the transmission and distribution system. The gas relay or bucholz relays is particularly important since it gives early warning of a slowly developing fault, permitting shutdown and repair before serious damage can occur. For short-circuit condition or internal faults, differential protective relays (DPR) are usually employed. In this project, SABER software simulator was used to implement solid-state digital-type components for the DPR. The project focused on the protection of 33/11 kv delta-wye transformer when internal fault happens. 3 packages solid-state digital-type DPR were designed to protect delta-wye transformer when internal fault happens. There are several problems encountered in this project where in SABER, 1) it is difficult to configure an initial values for delta-wye transformer due to obtain a desired outputs on wye-side, 2) 3-phase generator cannot do any partial changes either leading or lagging power factor, and 3) during circuit breakers switching, very high surges appear which can cause destruction to the power system components. Hence to reduce surges below the allowable maximum value during switching, this can be solve by implementing circuit breakers that not only works as a switch but also as impedance. Circuit breakers impedance can also be assume as an arc extinguisher. By extinguish the arc, the surges also will be reduce. Hence the results of this project are not only to isolate the delta-wye transformer from the generator and as well loads when fault happened, but is also capable to reduce surges during circuit breakers switching.